1999
DOI: 10.1029/1999gl900142
|View full text |Cite
|
Sign up to set email alerts
|

The 1997 Umbria‐Marche (Italy) earthquake sequence: Relationship between ground deformation and seismogenic structure

Abstract: Abstract. A field survey performed during the 1997 UmbriaMarche earthquake sequence led us to recognize ground and pavement ruptures associated with the three largest shocks (Mw_>5.7). The ruptures are concentrated in narrow bands that, in part, are on and near previously mapped high-angle normal faults. The geometry of the ground deformation is consistent with the NE-trending extension indicated by CMT focal solutions of the mainshocks.The distribution of aftershocks suggests that the three mainshocks occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 8 publications
4
51
0
Order By: Relevance
“…[73] measured few centimetres high strips of rejuvenation along the bedrock fault scarps and related these features to surface faulting; Cinti eta!. [74] interpreted the surface breaks as secondary ruptures along high-angle faults not directly related to the seismogenic source. A continuous surficial deformation has been derived from SAR interferometry and GPS which show the lowering of the Colfiorito basin due to the main shocks occurred on September 26 [75].…”
Section: Colfiorito Fault Systemmentioning
confidence: 99%
“…[73] measured few centimetres high strips of rejuvenation along the bedrock fault scarps and related these features to surface faulting; Cinti eta!. [74] interpreted the surface breaks as secondary ruptures along high-angle faults not directly related to the seismogenic source. A continuous surficial deformation has been derived from SAR interferometry and GPS which show the lowering of the Colfiorito basin due to the main shocks occurred on September 26 [75].…”
Section: Colfiorito Fault Systemmentioning
confidence: 99%
“…The area is seismically active, and earthquakes with local magnitude ranging between M L 4.6 and M L 5.8 have occurred repeatedly . The last earthquake sequence in the area occurred between May 1997and April 1998(AMATO et al, 1998EKSTRÖ M et al 1998;CINTI et al, (Table 1). Moreover, due to the geological and climatic settings, landslides are abundant in Umbria and contribute to shape the landscape (GUZZETTI et al, 1996(GUZZETTI et al, , 2008.…”
Section: Study Areamentioning
confidence: 99%
“…Although these shocks did not produce primary surface ruptures, the observed ground breaks (CINTI et al, 1999) identified a diffuse surface deformation along a 10-km-wide belt whose strike is in agreement with the The main shock occurred at 09:40 (M W ¼ 6.0; M 0 ¼ 1.26 · 10 25 dyne-cm) and accounts for about 50% of the total moment release in the sequence (EKSTRO¨M et al, 1998). The distribution of the moment release in several events of moderate size, instead of concentrating in a single large event, may be related to the structural complexity of the region.…”
Section: The 1997 Umbria-marche Italy Earthquake Sequencementioning
confidence: 99%